Do scientists know how to cite their peers? - Alves, Rômulo Romeu Nóbrega (Ethnobiology and Conservation, 2025)
Science is often portrayed as an objective and neutral endeavor. However, it is, in fact, permeated by moral and epistemological disputes. Rather than representing a homogeneous or entirely consensual field, scientific practice is marked by divergences that reflect different worldviews, values, and interests. These disputes extend beyond technical issues to encompass ethical and political questions—such as which knowledge is validated, which voices are heard, and which research agendas are prioritized.